Molecada no corre : comércio, experiência geracional e moral no Primeiro Comando da Capital - Silva, Evandro Cruz (2017)
This work is part of the contemporary debate on the relations between peripheral urbanity, illicit drug trade and criminalization in the state of São Paulo. The objective of this research is to analyze the generational transition in the Primeiro Comando da Capital (PCC), a Brazilian criminal group of great relevance in the last two decades (1990 - 2000). More specifically, I present some of the recent changes regarding this generational passage in the retail trade of illicit drugs in the context of PCC and on the basis of what would be the proceder [conduct mode of self and evaluation of the conduct of others guided by what is considered "Right " in certain contexts] as a moral mediator of everyday conflicts in the peripheries of the state of São Paulo. The data presented here were produced from the participant observation between 2014 and 2016, in a socio-educational center called here "Núcleo São Judas", located in a city of São Paulo west region called here "Pinheiros". We argue in this dissertation that the Primeiro Comando da Capital undergoes a generational transition, provided by the occupation of its positions of responsibility in the drug dealing by increasingly young subjects and by the resignifications of the concept of proceeding (characteristic sign of the moral ties related to the Comando) produced daily by these subjects.